Arctic Sea Ice in Two Configurations of the CESM2 During the 20th and 21st Centuries. Issue 9 (7th September 2020) - DeRepentigny, Patricia; Jahn, Alexandra; Holland, Marika M.; Smith, Abigail
Abstract: We provide an assessment of the current and future states of Arctic sea ice simulated by the Community Earth System Model version 2 (CESM2). The CESM2 is the version of the CESM contributed to the sixth phase of the Coupled Model Intercomparison Project (CMIP6). We analyze changes in Arctic sea ice cover in two CESM2 configurations with differing atmospheric components: the CESM2(CAM6) and the CESM2(WACCM6). Over the historical period, the CESM2(CAM6) winter ice thickness distribution is biased thin, which leads to lower summer ice area compared to CESM2(WACCM6) and observations. In both CESM2 configurations, the timing of first ice‐free conditions is insensitive to the choice of CMIP6 future emissions scenario. In fact, the probability of an ice‐free Arctic summer remains low only if global warming stays below 1.5°C, which none of the CMIP6 scenarios achieve. By the end of the 21st century, the CESM2 simulates less ocean heat loss during the fall months compared to its previous version, delaying sea ice formation and leading to ice‐free conditions for up to 8 months under the high emissions scenario. As a result, both CESM2 configurations exhibit an accelerated decline in winter and spring ice area, a behavior that had not been previously seen in CESM simulations. Differences in climate sensitivity and higher levels of atmospheric CO2 by 2100 in the CMIP6 high emissions scenario compared to its CMIP5 analog could explain why this winter ice loss was not previously simulated by the CESM. Plain Language Summary: We provide a first look at the current and future states of Arctic sea ice as simulated by the Community Earth System Model version 2 (CESM2), which is part of the newest generation of large‐scale climate models. The CESM2 model has two configurations that differ in their representation of atmospheric processes: the CESM2(CAM6) and the CESM2(WACCM6). We find several differences in the simulated Arctic sea ice cover between the two CESM2 configurations, as well as compared to the previous generation of the CESM model. Over the historical period, the CESM2(CAM6) model simulates a winter ice cover that is too thin, which leads to lower summer ice coverage compared to the CESM2(WACCM6) model and observations. In both CESM2 configurations, the probability of the Arctic becoming nearly ice free at the end of the summer remains low only if global warming stays below 1.5°C. In addition, the specific year a first ice‐free Arctic is reached is not sensitive to the future greenhouse gas emissions trajectories considered here. In contrast to the previous generation of the CESM, both CESM2 configurations project an accelerated decline in winter and spring ice area by the end of the 21st century if greenhouse gases emissions remain high. Key Points: The CESM2(CAM6) winter ice thickness distribution is biased thin and leads to a lower summer sea ice area than observed The timing of first Arctic ice‐free conditions in the CESM2 is independent of the choice of CMIP6 future emissions scenario By 2100, CESM2 shows an accelerated decline in winter and spring area under the high emissions scenario due to reduced fall ocean heat loss